Gender Differences in the Consequences of Divorce: A Study of Multiple Outcomes. - Leopold, Thomas (Demography (Springer Nature), 2018)
In this study, I examined gender differences in the consequences of divorce by tracing annual change in 20 outcome measures covering four domains: economic, housing and domestic, health and well-being, and social. I used data from the German Socio-Economic Panel Study (SOEP) and fixed-effects panel regression models on a sample of N = 18,030 individuals initially observed in a marital union, N = 1,220 of whom divorced across the observation period (1984-2015). Three main findings emerged from the analysis. First, men were more vulnerable to short-term consequences of divorce for subjective measures of well-being, but postdivorce adaptation alleviated gender differences in these outcomes. Second, a medium-term view on multiple outcomes showed more similarity than differences between women and men. The medium-term consequences of divorce were similar in terms of subjective economic well-being; mental health, physical health, and psychological well-being; residential moves, homeownership, and satisfaction with housework; and chances of repartnering, social integration with friends and relatives, and feelings of loneliness. Third, the key domain in which large and persistent gender differences emerged were women's disproportionate losses in household income and associated increases in their risk of poverty and single parenting. Taken together, these findings suggest that men's disproportionate strain of divorce is transient, whereas women's is chronic.